Investigation of a global mouse methylome atlas reveals subtype-specific copy number alterations in pediatric cancer models - Schoof, Melanie; Zheng, Tuyu; Sill, Martin; Imle, Roland; Cais, Alessia; Altendorf, Lea; Fürst, Alicia; Hofmann, Nina; Ernst, Kati; Vonficht, Dominik; Chan, Kenneth Chun-Ho; Holland-Letz, Tim; et al. (Nature genetics, 2026)
Copy number alterations (CNAs) are hallmarks of cancer, yet investigation of their oncogenic role has been hindered by technical limitations and missing model systems. Here we generated a genome-wide DNA methylation and CNA atlas of 106 genetic mouse models across 31 pediatric tumor types, including 18 new models for pediatric glioma. We demonstrated their epigenetic resemblance to human disease counterparts and identified entity-specific patterns of immune infiltration. We discovered that mouse tumors harbor highly recurrent CNA signatures that occur distinctly based on the tumor subgroup and driving oncogene and showed that these CNAs share syntenic regions with the matching human tumor types, thereby revealing a conserved but previously underappreciated role in subgroup-specific tumorigenesis that can be analyzed using the presented models. Our study provides insights into globally available mouse models for pediatric solid cancers and enables access to functional CNA interrogation, with the potential to unlock new translational targets in pediatric cancers.
Online veröffentlicht: 11. Dezember 2025
Gesehen am 20.02.2026